1. ## (Solved) Rearranging the formula

Hello,
Can anyone please show me how to rearrange the following formula making m the subject.

J = mv - mu

I am stuck before I start! You can't divide both sides by v, and you can't divide both sides by u (cuz that would make it worse!)

anyways the answer should be J / v-u , which takes me to the other doubt.
of you divide mv-mu by v-u (mv-mu/v-u), cancel out the v and u's giving m-m=0 (or is it m+m=2m?) either way it isn't m ...

2. Originally Posted by IBstudent
Hello,
Can anyone please show me how to rearrange the following formula making m the subject.

J = mv - mu

I am stuck before I start! You can't divide both sides by v, and you can't divide both sides by u (cuz that would make it worse!)

anyways the answer should be J / v-u , which takes me to the other doubt.
of you divide mv-mu by v-u (mv-mu/v-u), cancel out the v and u's giving m-m=0 (or is it m+m=2m?) either way it isn't m ...

One word: factor.
J = mv - mu = m(v - u)

Can you take it from here?

-Dan

Edit: $\displaystyle \frac{mv - mu}{v - u} \neq m - m$. When you cancel you have to cancel from both terms, not just one at a time. This is why you are getting a contradiction. A simpler example of this:

$\displaystyle \frac{6 \cdot 3 - 6 \cdot 2}{3 - 2} = 6 - 6 = 0$

but if you work out the numbers:
$\displaystyle \frac{6 \cdot 3 - 6 \cdot 2}{3 - 2} = \frac{18 - 12}{1} = 6$

You can see that the two are not equal.

3. why didn't I think of that!

,
,
,

,

,

,

,

,

,

,

,

,

,

,

# f=(v-u)/t make u subject of the formular

Click on a term to search for related topics.